Indigenous Science Dalam Pembuatan Pekasam Ikan (Fermentasi Ikan) Di Masyarakat Lokal Melayu Jambi - Miranda Oxtariani; Woro Sumarni; Sri Susilogati Sumarti; F Widhi Mahatmanti (Universitas Negeri Padang, 2022)
This study aims to reconstruct the knowledge of local wisdom of the Jambi Malay community, precisely in the village of Mangun Jayo, Tebo Regency making fish pekasam into scientific science knowledge in schools. This research method is descriptive qualitative through in-depth interviews, direct observation and document studies regarding the process of making fish pekasam The focus of this research is the tradition of making fish pekasam and the knowledge of craftsmen regarding raw materials and the manufacturing process. The data obtained are then analyzed, verified and constructed into a scientific knowledge that can be used as a learning resource in schools. In conclusion, there are 12 local wisdoms of the process of making pekasam that can be reconstructed into scientific knowledge.